Analisis Persepsi Wajib Pajak terhadap Implementasi Core Tax Administration System Ditinjau dari Relative Advantage (Studi Kasus PT XYZ) - Uleng, We Maryam Batari; Ekowati , Lia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The implementation of the Core Tax Administration System (CTAS) by the Directorate General of Taxes in Indonesia represents a significant shift toward a more digital and integrated tax administration system. However, in practice, several challenges have emerged, especially from the perspective of taxpayers as system users. This study aims to analyze the perception of PT XYZ a state owned enterprise as a corporate taxpayer regarding the implementation of CTAS in terms of relative advantage. It also explores perceived weaknesses of the system and assesses the effectiveness of related dissemination efforts. A qualitative descriptive approach with a case study method was employed, involving in-depth interviews with experienced tax staff. The analysis used Miles and Huberman's interactive model to identify key patterns. Findings indicate that CTAS offers a relative advantage primarily in the area of work convenience, such as improved accessibility to tax documentation and integration of payment and reporting processes. However, benefits in terms of speed, prestige, economic value, and system usability were found to be limited or insignificant. Key challenges identified include frequent system errors, server instability during peak periods, and rigid ID billing procedures. Moreover, the lack of adequate training and early socialization further hindered smooth adaptation. These findings underline the importance of user-centered improvements to ensure the long-term success of digital tax reform initiatives.